Weathering winter : a gardener's daybook - Klaus, Carl H. (Iowa City, IA : University of Iowa Press, 1997)
In winter, when the only things growing seem to be icicles and irritability, what pleasures exist for a gardener or for anyone who lives in a northern climate? In his distinctive daybook, Weathering Winter, Carl Klaus reminds readers that the season of brown twigs and icy gales is just as much a part of the year as when tulips open, tomatoes thrive, and pumpkins color the brown earth. From the first cold snap of late December 1994 to the first outdoor planting of onion sets and radish seeds in mid-March 1995, Klaus kept track of snow falling, birds flocking, soups simmering, gardening catalogs.
Acknowledgments; Winter: An Introduction; Weathering Winter; Summer Postscript
Print version record.
eBooks on EBSCOhost
Keywords: Klaus, Carl H. -- Diaries; Klaus, Carl H; Vegetable gardening -- Iowa -- Iowa City -- Anecdotes; Gardeners -- Iowa -- Iowa City -- Anecdotes; Winter -- Iowa -- Iowa City -- Anecdotes; Horticulture potagère -- Iowa -- Iowa City -- Anecdotes; Jardiniers -- Iowa -- Iowa City -- Anecdotes; Hiver -- Iowa -- Iowa City -- Anecdotes; GARDENING -- Reference; GARDENING -- Essays; GARDENING -- Vegetables; SCIENCE -- Life Sciences -- Horticulture; GARDENING -- General; Gardeners; Vegetable gardening; Winter; Iowa -- Iowa City; Anecdotes; Diaries